Trauma Imaging of the Acute Cervical Spine - Berritto, Daniela; Pinto, Antonio; Michelin, Paul; Demondion, Xavier; Badr, Sammy (Seminars in Musculoskeletal Radiology, 2017)
Among patients admitted in emergency departments for acute cervical spine trauma, only a few have a confirmed and significant injury requiring surgical intervention. Imaging plays a key role in screening for unstable lesions that can be responsible for devastating neurologic complications or death. The complex anatomy of the cervical spine is associated with a wide spectrum of osseous and ligamentous pathologies. This review focuses on the imaging features of the main cervical spine fractures that can be encountered in emergency radiology.
Keywords: cervical spine; trauma; diagnostic imaging; emergency radiology